LEGAL AND HUMAN RIGHTS IMPLICATIONS OF THE UNEXECUTED DEATH PENALTY IN INDONESIA BASED ON THE PRINCIPLE OF HUMANITY - Rafa Reihan Pradipa; Anis Widyawati (Universitas Negeri Semarang, 2026)
The death penalty is still maintained within the Indonesian criminal justice system as the most severe form of punishment for extraordinary crimes such as terrorism, narcotics offenses, premeditated murder, and corruption. However, the implementation of the death penalty in Indonesia raises serious legal issues, particularly regarding the prolonged waiting period for execution, which lacks legal certainty. Death row inmates are often required to endure years of uncertainty before execution, even after a final and binding court decision has been rendered. This condition gives rise to legal implications and violations of human rights, especially the right to life, the right to legal certainty, and the right to humane treatment. The prolonged delay in carrying out death sentences potentially causes severe psychological suffering, commonly referred to as the death row phenomenon and death row syndrome, which contradict the principle of humanity as a fundamental value in the formation and enforcement of law in Indonesia. This research employs a normative legal research method using statutory, conceptual, and case approaches to analyze the legal basis of the death penalty and its legal and human rights implications for death row inmates whose executions are indefinitely delayed. The findings indicate that the absence of clear regulations regarding the execution waiting period results in legal uncertainty and violations of the principle of humanity. Although the 2023 Criminal Code introduces conditional death penalty with a ten-year probation period as a moderating approach, such regulation has not fully resolved issues related to psychological suffering and legal certainty for death row inmates. Therefore, comprehensive regulatory reform is necessary to ensure legal certainty, human rights protection, and respect for humanitarian values in the implementation of the death penalty in Indonesia.